Etiopathogenesis and clinical manifestations of the non-ketotic feline diabetes mellitus - SARIDOMICHELAKIS (Μ. Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Diabetes mellitus, the clinical syndrome that results form absolute or relative insulin deficiency and/or reduced number or sensitivity of the insulin receptors, is considered one of the most common endocrine diseases in the cat, being secondary only to hypethyroidism. The exact etiology of type I feline diabetes mellitus remains obscure, although in many cases occurs secondarily to chronic pancreatitis. Type II diabetes mellitus, which is very common in the everyday clinical practice, is characterized by relative insulin deficiency, secondary to reduced production of this hormone (chronic pancreatitis, pancreatic amyloidosis), insulin resistance and/or increased glucose production by the liver (obesity, chronic stress, overproduction of amylin). Secondary (type III) diabetes mellitus is the result of various causes, not directly involving pancreatic tissue, that cause insulin resistance, such as hyperadrenocorticism, pheochromocytoma, acromegaly, hyperthyroidism, infections, neoplasia, hyperlipidemia, chronic heart and renal failure and the exogenous administration of glucocorticoids and progestagens. The most common clinical manifestations of feline non-ketotic diabetes mellitus include polyuria, polydipsia, polyphagia, weight loss, hepatomegaly, retinopathy, peripheral polyneuropathy, dry seborrhea and those resulting form the secondary infections, such as cystitis and stomatitis.